Global Exponential Stability of Learning-Based Fuzzy Networks on Time Scales - Juan Chen; Zhenkun Huang; Jinxiang Cai (Abstract and Applied Analysis)
We investigate a class of fuzzy neural networks with Hebbian-type unsupervised learning on time scales. By using Lyapunov functional method, some new sufficient conditions are derived to ensure learning dynamics and exponential stability of fuzzy networks on time scales. Our results are general and can include continuous-time learning-based fuzzy networks and corresponding discrete-time analogues. Moreover, our results reveal some new learning behavior of fuzzy synapses on time scales which are seldom discussed in the literature.